Induction therapy with rabbit antithymocyte globulin versus basiliximab after kidney transplantation: a health economic analysis from a German perspective - Cremaschi, Liana; von Versen, Regina; Benzing, Thomas; Wiesener, Michael; Zink, Nikolai; Milkovich, Gary; Paivanas, Thomas; Gallagher, Meghan; Thaiss, Friedrich (Transplant International, 2017)
A health economic analysis was undertaken based on the 1-year database from a randomized study of rabbit anti-human thymocyte immunoglobulin (rATG) versus basiliximab, in kidney transplantation using resource utilization data and cost estimates from three German hospitals. A three-state Markov model was applied to estimate cost-effectiveness to 10 years post-transplant. Total mean treatment cost per patient to year 1 post-transplant was EUR62 075 vs. EUR59 767 for rATG versus basiliximab (P < 0.01). rATG therapy was associated with similar treatment costs to basiliximab by year 2, and a predicted cumulative treatment cost saving of EUR4 259 under rATG versus basiliximab by year 10 post-transplant. The mean number of quality-adjusted life years (QALYs) per patient by year 1 was 0.809 vs. 0.802 in the rATG and basiliximab cohorts, respectively (P = 0.38), with cumulative QALYs of 6.161 and 6.065 per patient by year 10. By year 2, the cumulative cost per QALY was slightly lower under rATG (EUR35 378) than basiliximab (EUR35 885), progressing to a saving of EUR1 041 under rATG for the cumulative cost per QALY by year 10. In conclusion, this model indicates that rATG induction provides a modest increase in QALYs with lower long-term costs than basiliximab in deceased-donor high-risk kidney transplant patient
EVALuna2:3963